The legal nature of regional currency: theory, history and practice of monetary circulation in selected countries of the world - I. B. Lagutin (Правоприменение, 2023)
The subject. The article discusses regional currencies from the point of view of their definition in the system of monetary circulation, purpose, experience in the legal regulation of the circulation of regional currencies in certain territories of various states, the goals and objectives of regional monetary circulation are studied, and the impact of such circulation on the economy of a particular territory is determined. The article reveals the main differences between regional currencies and the national (official) currencies of the state, assesses the overall effectiveness of the development of regional money circulation. The paper analyzes the legal nature of regional currencies, using the example of individual currencies, namely, it raises the question of which legal nature dominates in regional currencies – private law or public law.  Methodology. In the course of the study, various general scientific and special scientific methods of cognition were used, the most important of which were methods - historical and legal, comparative historical, comparative legal, as well as the method of referring to other social sciences, such as economics.Main results. In the course of the study, the legal nature of regional currencies was redistributed, using the example of the practice of issuing such currencies in various countries with different periods of historical development.Conclusions. The study found that the introduction of regional currencies into circulation in different periods of time had a variety of purposes. In modern times, these are the goals of protecting the local economy and business from transnational companies and global crises, developing the local economy through greater circulation of funds within a particular territory (from infrastructure development to increasing domestic traffic), reducing capital outflows, developing tourism, and much more. It is also concluded that the legal nature of regional money is not precisely defined. So, on the one hand, the state has a monopoly on the issue of money, and on the other hand, the law protects the freedom to conclude an agreement, which may provide for, among other things, the issue of regional money as a condition for the implementation of the agreement, which is currently used by individual municipalities in various countries of the world.